KEBIJAKAN PENGATURAN PERDAGANGAN KARBON SEBAGAI UPAYA MITIGASI PERUBAHAN IKLIM SEKTOR KEHUTANAN DI NTB: Policy on Regulating Carbon Trading as an Effort to Mitigate Climate Change in the Forestry Sector in NTB - Satriawan, Hera Alvina; Alqindy, Fatria Hikmatiar; Umami, Allan Mustafa; Wahyuddin, Wahyuddin (Ganec Swara, 2025)
The policy of regulating carbon trading as an effort to mitigate climate change in the forestry sector in NTB still faces legal and normative obstacles in its implementation. The objectives of this study are to review the legal framework concerning carbon trading as a climate change mitigation instrument in the forestry sector and to identify the juridical and normative constraints encountered in implementing the carbon trading policy in the NTB forestry sector. This study employs a normative legal research method which examines law as norms, rules, and doctrines, aiming to answer the legal problems investigated. The approaches utilized are the Statute Approach and the Conceptual Approach. Secondary data was used, consisting of primary legal materials (legislation), secondary (scholarly opinions), and tertiary (legal dictionaries). The analysis was conducted qualitatively using an inductive-deductive reasoning pattern to draw significant conclusions. The findings indicate that forest-based carbon trading emerges as a potential innovative financing opportunity to support the sustainability of Social Forestry programs, addressing the lack of financial support that has long been a challenge. Carbon trading regulation must be viewed as part of an environmental governance mechanism that demands certainty, transparency, and fairness among actors. Therefore, the implementation of this policy must ensure community participation and the integration of regulations to prevent legal disharmony at the local implementation level.